New palladium(II) complexes with pyrazole ligands Part II. Synthesis, spectral and thermal studies, and antitumor evaluation - Barra, Carolina V. [UNESP]; Rocha, Fillipe V. [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Frem, Regina Célia Galvão [UNESP]; Mauro, Antonio Eduardo [UNESP]; Carlos, Iracilda Z. [UNESP]; Ananias, Sandra R. [UNESP]; Quilles, Marcela B. [UNESP] (Springer, 2011)
This study describes the synthesis, IR, (1)H, and (13)C{(1)H} NMR spectroscopic as well the thermal characterization of the new palladium(II) pyrazolyl complexes [PdCl(2)(HmPz)(2)] 1, [PdBr(2)(HmPz)(2)] 2, [PdI(2)(HmPz)(2)] 3, [Pd(SCN)(2)(HmPz)(2)] 4 {HmPz = 4-methylpyrazole}. The residues of the thermal decomposition were identified as Pd(0) by X-ray powder diffraction. From the initial decomposition temperatures, the thermal stability of the complexes can be ordered in the sequence: 1 > 2 > 4 a parts per thousand 3. The cytotoxic activities of the complexes and the ligand were investigated against two murine cancer cell lines: mammary adenocarcinoma (LM3) and lung adenocarcinoma (LP07) and compared to cisplatin under the same experimental conditions.
Keywords: DTA; Palladium(II); Pyrazoles; Spectroscopy; TG